Improvement of Lead Acetate-Induced Testicular Injury and Sperm Quality Deterioration by Solanum Anomalum Thonn. Ex. Schumach Fruit Extracts in Albino Rats - Samuel James Offor; Herbert Orji Mbagwu; Orish Ebere Orisakwe (Tehran University of Medical Sciences, 2019)
Objective: This study has investigated the protective role of a natural alternative, Solanum anomalum fruit extract in lead induced testicular toxicity in male albino rats. Materials and methods: Twenty-four mature male albino rats were used, divided into four groups of six rats per group. Group 1 (control rats) were given distilled water (10ml/kg), group 2 received lead acetate solution 60mg/kg, group 3 received lead acetate (60mg/kg) followed by Solanum anomalum (452mg/kg) and group 4 rats were given lead acetate (60mg/kg) followed by Solanum anomalum  (678mg/kg) by oral gavage daily for 28 days. Results: Lead treated group showed significant increase in Malondialdehyde MDA (1.58 ± 0.09 to 1.90 ± 0.17 µmol/L of plasma) and decreases in Superoxide dismutase SOD, glutathione peroxidase (482.85 ± 53.43 to 247.18 ± 70.40 U/L of blood), total glutathione (1.11 ± 0.03 to 0.56 ± 0.31 ng/µL) (144.80 ± 7.00 and 122.39 ± 4.63 U/ml of blood), epididymal sperm reserve, testicular sperm count, % sperm motility and % sperm viability. Conclusion: Co-administration of Solanum anomalum significantly reversed the effect of lead with restoration of histoarchitecture of the testes. Solanum anomalum may be a protective modulator of lead -induced testicular injury.